China's Urban Health Care Reform: From State Protection to Individual Responsibility - Wong, Chack-kie; Lo, Vai Io; Tang, Kwong-leung (Lexington Books, 2005)
One way to describe the importance of social policy is to say it's about 'what is and what might be.' This ethos is the driving force behind Chack-Kie Wong, Vai Io Lo, and Kwong-leung Tang's China's Urban Health Care Reform. Based on a study of a mid-level city in China, these three scholars provide analysis and offer theory-based recommendations on health care development. Using a comparative policy framework, supported by a legal expert's knowledge of regulatory specifications, China's Urban Health Care Reform argues that a strategy with priority in economic growth, as in the case of China, does not bring forth cost efficiency and equity in health care for the whole nation. Ultimately, Wong, Lo, and Tang strive to offer direction for health care reform that will lead to better health care in China's cities. As a result, this is a work of great significance to anyone involved in public health, social work, public policy, medicine, or law.